The influence of energy transition, and natural resources on carbon emissions in China: an augmented ARDL application - Amin A.; Yusoff N.Y.M.; Peng S.; I??k C.; Ullah A.; Akbar M. (Springer Science and Business Media B.V., 2025)
According to the 26th United Nations Climatic Change Conference (COP26), the deteriorating climate situation has increased the frequency of extreme weather conditions around the globe. An increase in the use of fossil energies, the depletion of natural resources, and the release of carbon dioxide into the atmosphere are the primary contributors to climate change. China has emerged as the global leader in energy consumption and carbon emissions, owing to its remarkable pace of economic development. To being carbon neutral by 2060, it should utilize natural resources wisely and promote energy transition. Renewable energy and the efficient use of natural resources are effective means of facilitating the shift to a low-carbon economy. Critical to China?s transition to a carbon-free economy and sustainable development is a comprehensive analysis of the factors that drive this progress. Within the scope of this discussion, examining the influence of the abundance of natural resources, the energy transition, economic growth, and urbanization on carbon dioxide emissions is important. To end this, an augmented ARDL approach is used on the dataset from 1990 to 2019 for China. The outcomes of this research demonstrate that a rise in urbanization and real income causes environmental degradation, whereas increasing renewable energy diminishes carbon emissions. Moreover, the correlation among natural resource abundance and carbon emissions is positive. We urge Chinese policymakers to secure the sustained utilization of natural resources to decrease reliance on polluting energy sources, and establish stability among ecological and economic policies to reduce environmental destruction and protect the atmosphere for the long term. Furthermore, understanding how China?s energy transition, natural resources, and carbon emissions interact intricately is crucial to our worldwide effort to combat climate change. We may find paths towards a more sustainable and ecologically aware future for China and the globe by comprehending the causal links and recognizing possible synergies between these issues. ? 2024, The Author(s), under exclusive licence to Springer Nature B.V.